The actions of the state in the production of cultural heritage the treatment of a cultural icon as bearer of values, identity and meaning at Groot Constantia in Cape Town - Leibman, Yvonne (Department of Civil Engineering, 2014)
Includes abstract. Includes bibliographical references.